The potential for typhoon impact on bird populations on the island of Rota, Northern Mariana - Ha, C. (Micronesica, 2012)
Numerous independent analyses of climate change have suggested that changing weather patterns are resulting in increasing frequency or intensity of hurricanes and typhoons. We explore the relationship between cyclonic event frequency and severity on measures of bird abundance on the island of Rota, in the Northern Mariana Islands to determine if changes in cyclonic event pattern might be related to the local decline of avian species. We developed a database of Rota cyclonic event encounters since 1952 and three primary variables for analysis of cyclonic event behavior were then derived from this data: Time-Between-Typhoon-Encounters, Distance from Rota at closest approach, and Pressure at the center of the cyclonic event at the point of closest approach Three similar smoothed variables were derived relative to each Breeding Bird and Variable Circle Plot census time point. Multivariate general linear models were constructed separately for each bird abundance data set with multiple species as dependent variables and smoothed cyclonic event time-between-encounter, distance-at-closest- point, and central-pressure-at-closest-point as independent variables. Cyclonic event behavior in relation to Rota did not exhibit an increase in frequency, as sometimes perceived, but did show a significant decrease in distance to the island and an increase in intensity as measured by central pressure. Several species abundances showed significant relationships with cyclonic event pressure or distance, including the Mariana Crow, Philippine Turtle Dove, and Rufous Fantail. It appears that changes in cyclonic event “behavior” could be impacting forest-bird populations on Rota. Overall, bird population declines may be due to a combined effect of habitat loss, introduced species pressure, and cyclonic events, where any one of the factors might be enough to tip a species into decline.